PRAGMATIC ANALYSIS OF DIRECTIVES IN FOOD RECIPES - QasimObayes Al-Azzawi, Ali Hussein Abdulameer (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Language is human universal tool of communication, food on the other hand is also considered as a tool of cultural transmission. Both language and food can be explored by using culinary linguistics. The term culinary linguistics is a field of applied linguistics which is concerned bout food and food recipes. The language of food recipes is very rich one. Thus, the current study aims at exploring the nature of food recipes text more specifically the use of "directives". The study also hypothesis that directiveness is the most commonly used techniques in the context of food recipes. The study will adopt Seale’s speech act theory as a model of analysis, due to its close relevance to the nature of the contexts under investigation. The data of the study consists of different food recipes that are collected randomly from the most popular international food site. The value of the study lies in exploring the nature of food recipes texts, more particularly the use of directives in these texts. And to find out the role of directiveness in the food recipes texts. The study find out that directness play a crucial role in this type ofdiscourse.